Future professional communication in astronomy II - Acomazzi, Albertio (New York Springer, 2011)
FPCA-II Opening Comments -- Astronomical Publishing: Yesterday, Today, and Tomorrow (A. Heck/Strasbourg Obs.) -- The Emergin Scholarly Brain (M.J. Kurtz/CfA) -- Communicating Astronomy Beyond IYA2009 (R.T. Fienberg/AAS) -- Trends in Scientific Publishing at Springer (G. Eichhorn/Springer) -- Astronomy Journal Publishing: Serving the Community (R. Boucher/Wiley-Blackwell) -- Publishing in Greater Depth: Article of the Future and Beyond (D. Clark/Elsevier) -- Publishing Astronomy and Astrophysics: Article Numbering, Electronic First (M.L. Chaix/EDP Sciences) -- The Future of the ASP Conference Series (J. Jensen et al./ASP) -- Astronomical Publication Rates in the US, UK, and Europe (H. A. Abt/KPNO) -- Fully Digital: Policy and Process Implications for the AAS (Chr. Biemesderfer/AAS) -- The Present and Future of The Astrophysical Journal (E. Vishniac/McMaster Univ.) -- Open Access: Current Status, AAS Perspectives (K. Marvel and Chr. Biemesderfer/AAS) -- Open Access Publishing in High-Energy Physics: The SCOAP3 Initiative (S. Mele/CERN) -- Astronomy Librarians - Quo Vadis? (J. Lagerstrom/STScI and U. Grothkopf/ESO) -- Telescope Bibliometrics 101 (U. Grothkopf/ESO and J. Lagerstrom/STScI) -- Progress on the 'Declaration Concerning the Evolving Role of Libraries in Research Centres' (T.J. Mahoney/IAC) -- Finding Your Literature Match - A Recommender System (E.A. Henneken et al./SAO) -- Linking Literature and Data: Status Report and Future Efforts (A.Accomazzi/CfA) -- FPCA-II Concluding Remarks (M.J. Kurtz/CfA).
FPCA-II Opening Comments -- Astronomical Publishing: Yesterday, Today, and Tomorrow (A. Heck/Strasbourg Obs.) -- The Emergin Scholarly Brain (M.J. Kurtz/CfA) -- Communicating Astronomy Beyond IYA2009 (R.T. Fienberg/AAS) -- Trends in Scientific Publishing at Springer (G. Eichhorn/Springer) -- Astronomy Journal Publishing: Serving the Community (R. Boucher/Wiley-Blackwell) -- Publishing in Greater Depth: Article of the Future and Beyond (D. Clark/Elsevier) -- Publishing Astronomy and Astrophysics: Article Numbering, Electronic First (M.L. Chaix/EDP Sciences) -- The Future of the ASP Conference Series (J. Jensen et al./ASP) -- Astronomical Publication Rates in the US, UK, and Europe (H. A. Abt/KPNO) -- Fully Digital: Policy and Process Implications for the AAS (Chr. Biemesderfer/AAS) -- The Present and Future of The Astrophysical Journal (E. Vishniac/McMaster Univ.) -- Open Access: Current Status, AAS Perspectives (K. Marvel and Chr. Biemesderfer/AAS) -- Open Access Publishing in High-Energy Physics: The SCOAP3 Initiative (S. Mele/CERN) -- Astronomy Librarians - Quo Vadis? (J. Lagerstrom/STScI and U. Grothkopf/ESO) -- Telescope Bibliometrics 101 (U. Grothkopf/ESO and J. Lagerstrom/STScI) -- Progress on the 'Declaration Concerning the Evolving Role of Libraries in Research Centres' (T.J. Mahoney/IAC) -- Finding Your Literature Match - A Recommender System (E.A. Henneken et al./SAO) -- Linking Literature and Data: Status Report and Future Efforts (A.Accomazzi/CfA) -- FPCA-II Concluding Remarks (M.J. Kurtz/CfA).
Electronic reproduction.
Keywords: Astronomical literature -- Congresses; Electronic books